Debe tipificarse en el código penal como conducta delictiva autónoma, la falsa autoincriminación de un delito. - Gracia Sanabria, Celiano George (2011)
When culminating my career of Right and to prepare to obtain Lawyer's title, my great concern has been the levels of insecurity and crime rate that our country lives. The State doesn't have an integral criminal politics as strategy to face this phenomenon, the levels of crime rate have overcome that capacity, arriving from the intellectual responsibility and material of the crime, the complicity, the concealment and until the false autoinculpación, to distract and to deceive to the justice for it the necessity of this study that allows me to investigate and to propose alternative of solution to the outlined problem. The action field is bounded to the causes of Reforming the Penal Code in the I surrender of the crimes, the false autoinculpación of a crime. In the development of the present work you revises bibliography with respect to the topic and other materials, with the purpose of recabar information that he/she helps to understand in a better way the study object. The investigation mark is governed to the right and the necessity of the effective justice. The methodology used to a field investigation, documental and experimental of historical and correctional descriptive, explanatory type, the inductive method of descriptive type, through the deductive method and by means of the analytic method, we observe general cases, for the execution I used methods of empiric level as the survey and the interview; the mathematical method for the I calculate of the stratified sample, 100% that corresponds Lawyers in free exercise, so much of the County of Emeralds like of Loja, the statistical method with which demonstrates the results in terms of percentages. The information was processed through the tabulation, analysis and interpretation of the results in statistical graphic squares. You selects the most outstanding information for the hypothesis confirmation and recommendations for the new reformation of the Penal Code.